The Education Assessment Competence Structure of Primary Teachers in Vietnam - Nguyen, Cong Khanh (H. : ĐHQGHN, 2019)
Education assessment is considered to be indispensable competence for teachers at all levels. However, there are currently many difficulties in assessing this competence, especially for primary teachers when there is a change in assessing students. In this report, we would like to suggest an education assessment competence structure for primary teachers and to demonstrate such structure through a survey of primary teachers' assessment competences in Vietnam. Survey results have shown that the education assessment competence structure consists of 6 component competencies which suitable for primary teachers in Vietnam. And, the report also points out that Vietnamese primary teachers' education assessment competences in Vietnam is currently evaluated.